2011
DOI: 10.3109/1354750x.2010.546013
|View full text |Cite
|
Sign up to set email alerts
|

Differential exposure biomarker levels among cigarette smokers and smokeless tobacco consumers in the National Health and Nutrition Examination Survey 1999–2008

Abstract: Assessment of biomarkers is an appropriate way to estimate exposure to cigarette mainstream smoke and smokeless tobacco (SLT) constituents in tobacco consumers. Using the US National Health and Nutrition Examination Survey (NHANES, 1999-2008), biomarkers of volatile organic compounds, halogenated aromatic hydrocarbons (HAHs), polycyclic aromatic hydrocarbons (PAHs), acrylamide, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), and metals were evaluated. In general, biomarker levels in SLT consumers were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
4
18
0
Order By: Relevance
“…This result is consistent with previous analysis of NHANES data (17). Further research on this topic is needed to establish that smokeless tobacco is the cause of these elevated lead levels among users and, if so, to identify the elements of smokeless tobacco production that contribute to these higher levels.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This result is consistent with previous analysis of NHANES data (17). Further research on this topic is needed to establish that smokeless tobacco is the cause of these elevated lead levels among users and, if so, to identify the elements of smokeless tobacco production that contribute to these higher levels.…”
Section: Discussionsupporting
confidence: 94%
“…Hecht et al (16) subsequently found, using data from the three studies of smokeless tobacco users in the Twin Cities area, that cotinine and NNAL concentrations were significantly associated with years of smokeless tobacco use. Naufal et al (17), on the other hand, analyzed biomarkers of volatile organic compounds, halogenated aromatic hydrocarbons, polycyclic aromatic hydrocarbons, acrylamide, NNAL, and metals from 368 smokeless tobacco users, 5,040 cigarette smokers, and 16,443 nonconsumers of tobacco and nicotine replacement therapy products from US National Health and Nutrition Examination Survey (NHANES) participants from 1999-2008. The authors concluded that biomarker concentrations were generally significantly lower among smokeless tobacco users compared with smokers, with the exception of NNAL and some halogenated aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current analysis were also consistent with previous reports that have indicated that urinary arsenic concentrations in cigarette smokers and nonconsumers of tobacco are not different (Gebel et al, 1998;Heck et al, 2009;Richter et al, 2009) and in cigarette smokers, SLT consumers, and non-consumers of tobacco (Naufal et al, 2011). Additionally, results from Naufal et al (2011) showed that in cigarette smokers, the relationship between urine total arsenic and serum cotinine (a metabolite of nicotine and marker of tobacco exposure) was negative, and in SLT consumers, urinary total arsenic was not correlated with serum cotinine. This provides additional evidence of no relationship between arsenic and (frequency or intensity of) tobacco consumption.…”
Section: Discussionsupporting
confidence: 94%
“…The geometric mean concentrations presented in this analysis were consistent with urinary arsenic concentrations previously published for the US population based on NHANES 2003NHANES -2004., for individuals 20 years and older, mean total arsenic, DMA, and arsenobetaine were 8.64, 3.79, 1.79 lg/g creatinine, respectively (Caldwell et al, 2009). The results of the current analysis were also consistent with previous reports that have indicated that urinary arsenic concentrations in cigarette smokers and nonconsumers of tobacco are not different (Gebel et al, 1998;Heck et al, 2009;Richter et al, 2009) and in cigarette smokers, SLT consumers, and non-consumers of tobacco (Naufal et al, 2011). Additionally, results from Naufal et al (2011) showed that in cigarette smokers, the relationship between urine total arsenic and serum cotinine (a metabolite of nicotine and marker of tobacco exposure) was negative, and in SLT consumers, urinary total arsenic was not correlated with serum cotinine.…”
Section: Discussionsupporting
confidence: 93%
“…2A and 2B). Results from previous studies have indicated U-Cd and B-Cd concentrations are higher in cigarette smokers than in non-smokers and SLT consumers, and that increasing B-Cd and U-Cd in cigarette smokers are associated with increasing serum or urine cotinine concentrations (Naufal et al, 2011;Shaham et al, 1996;Willers et al, 1992).…”
Section: Discussionmentioning
confidence: 94%